Linear IgA bullous dermatosis in adults and children: a clinical and immunopathological study of 38 patients - Genovese, Giovanni (Orphanet J Rare Dis, 2019)
BACKGROUND: Linear IgA bullous dermatosis (LABD) is a rare autoimmune subepithelial vesiculobullous disease due to IgA autoantibodies directed against different antigens of the basement membrane zone (BMZ) of the skin and/or mucosae. It affects mainly preschool-aged children and adults, with only few studies on large series. The aim of this study was to assess possible differences between adults and children regarding clinical presentation, immunopathologic features, management and course of the disease. METHODS: A retrospective review of 38 LABD patients, followed-up from November 2006 to September 2018, was performed. RESULTS: Of 38 patients, 27 were adults and 11 children. Mean age at diagnosis was 5.4 years and 60.6 years in the pediatric and adult group, respectively. Considering both groups, limbs were the most commonly involved site (73.7%), followed by trunk (55.3%), head (36.8%) and buttocks (13.2%). Interestingly, head (p = 0.008), particularly perioral (p = 0.001), involvement, as well as “string of pearls” arrangement (p = 0.03), were more prevalent in children. Mucosal involvement was seen in 9 (23.7%) patients and was more frequent in children than adults (45.5% vs 14.8%, respectively, p = 0.09). Linear IgA deposits along the BMZ were observed in 30 patients (78.9%), while linear/granular IgA deposits in 8 patients (21.1%). Dapsone was the most commonly used drug (78.9%) and complete remission was achieved in most cases (81.6%). CONCLUSIONS: Our epidemiological and clinicopathological findings relative to a large cohort of LABD patients are mostly consistent with the literature data. Interestingly, head, notably perioral, involvement and “string of pearls” arrangement occurred more frequently in the paediatric than adult group. The above clinical parameters may be regarded as diagnostic tools for LABD in children. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13023-019-1089-2) contains supplementary material, which is available to authorized users.